Beyond Legislative Ceremony: Fathi Osman’s Shura and the Meaningful Participation Mandate in Indonesian Lawmaking - Hantoro, Bimo Fajar (Al-'Adl, 2026)
This paper aims to analyze the meaningful participation mandate in lawmaking, especially its codification in Law 13/2022, within the framework of Fathi Osman’s conception of shura. Employing doctrinal legal method with statutory and conceptual approaches, this paper presents a novel conceptual parallel. The findings demonstrate that the three pillars of the meaningful participation mandate, including the right to be heard, the right to be considered, and the right to be explained, are the direct legal-procedural operationalization of shura’s core substantive principles of mandatory consultation, binding deliberation, and effective, non-ceremonial participation. However, Law 13/2022 constitutes a half-hearted codification effort of the mandate. This is most evident in its framing of the pivotal right to be explained as a discretionary exercise for lawmakers rather than an obligatory one. This flaw severs public accountability, renders participation merely ceremonial, and robs public input of its substantive deliberative power. This substantive failure not only contravenes the meaningful participation mandate, but also the shura obligation, making the process incapable of achieving its ultimate goal of maslaha. This paper concludes by proposing specific amendments to Law 13/2022, making the right to be explained mandatory and strengthening the right to be heard by requiring explanatory statements to ensure public intelligibility, not just legal access.